Bi-directional DC Charging Stations for EVs on renewable-powered LVDC Grids: Design, Sizing, Control and Testing - Gutwald, Benjamin; Lehmann, Raphael; Barth, Martin; Reichenstein, Tobias; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility, EPTS 2024, 2024)
E-mobility has undergone a remarkable transformation in recent years. It has progressed from the early days of a few electric vehicles (EVs) to widespread acceptance and integration into society. In the effort to address climate change, it has also become a necessity. The advancement in battery technology has enabled these EV not only to have better performance and longer ranges but also the capability to function as energy storage units for both households and businesses. This feature can prove valuable in industrial fleets, contributing substantially to grid stability and financial savings through temporary renewable energy storage and peak load balancing. DC grids provide the most flexible, efficient, and environmentally friendly charging architecture. Ideally, they are supplied directly from renewable energy generators. While bidirectional charging station prototypes for AC networks are emerging, solutions for future DC grids are still lacking.This publication evaluates the potential of this novel supply architecture and derives requirements for the regulatory-compliant design and commissioning of DC-coupled bidirectional direct current (DC) charge points (CPs). Furthermore, a proposal for the selection, dimensioning and interconnection of the electrical components, as well as the associated control and communication architecture of a corresponding power scalable charger is presented. This also includes the meaningful integration into an industrial DC grid, including the backend communication with the associated energy management system (EMS), which also plays a decisive role in the exploitation of the potential of the technology. In the first test phase of the charging station, a power-hardware-in-The-loop EV simulation will be carried out in conjunction with a regeneratively fed industrial low voltage direct current grid until standardized solutions for bidirectional EVs are actually available on the market.
CRIS-Team Scopus Importer:2024-08-02
Keywords: bidirectional charging; Direct current grid; LVDC; smart grid; V2G